RANCANG BANGUN TRAINER ROBOT LENGAN UNTUK PRAKTIKUM ROBOTIKA PADA PRODI S1 TEKNIK ELEKTRO FAKULTAS TEKNIK UNIVERSITAS TADULAKO - Prasetyo, Bayu Putra; Fauzi, Rizana; Subito, Mery; Ardias, Erwin; Mustari, Aidynal (Foristek, 2024)
Robotic arms are a type of robot that is currently developing rapidly in industry, this has caused robotics technology to become one of the mandatory subjects taught in universities. In the Undergraduate Department of Electrical Engineering, Faculty of Engineering, Tadulako University, the robotics course is a mandatory subject studied by students, especially students who take the weak current concentration (TEN). This research aims to provide students with an understanding of how to control a robot arm. The design of a robot arm system with 4 degrees of freedom is made using several types of control such as control using Arduino IDE software, push buttons and potentiometers. The results of testing the robot arm trainer after controlling it with three types of control were successful. In the first control using the Arduino IDE software control it shows that the direction of rotation of the motor rotates according to the program target given, in the second control using a push button it shows that the speed and acceleration are directly proportional to changes in motor degrees, then in the third control using a potentiometer it shows that the degree mapping on the potentiometer is directly proportional to the degree of the stepper motor. However, in the test there were differences in degree values ​​when the motor rotated which caused the resulting data to be inaccurate. This is due to a mismatch in tooth size between the belt and the stepper motor gear, causing wear on the belt.